2007
DOI: 10.3390/s7081462
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Sensor for Determination of Genetically Modified Soybean Roundup Ready (R) in Samples not Amplified by PCR

Abstract: Abstract:The chemically modified piezoelectrodes were utilized to develop relatively cheap and easy to use biosensor for determination of genetically modified Roundup Ready soybean (RR soybean). The biosensor relies on the immobilization onto gold piezoelectrodes of the 21-mer single stranded oligonucleotide (probes) related to 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) gene, which is an active component of an insert integrated into RR soybean genome. The hybridization reaction between the probe and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 45 publications
(44 reference statements)
0
30
0
Order By: Relevance
“…These sensors enabled the identification of transgenic soy by means of probes specific to the P35S and NOS terminator sequence . A probe binding to the EPSPS gene sequence itself can also be used for the identification of a transgenic soy variety . Piezoelectric sensors also detected allergens found in shrimps .…”
Section: Allergenic Additives and Methods Of Their Detection In Procementioning
confidence: 99%
See 2 more Smart Citations
“…These sensors enabled the identification of transgenic soy by means of probes specific to the P35S and NOS terminator sequence . A probe binding to the EPSPS gene sequence itself can also be used for the identification of a transgenic soy variety . Piezoelectric sensors also detected allergens found in shrimps .…”
Section: Allergenic Additives and Methods Of Their Detection In Procementioning
confidence: 99%
“…The transducer constitutes the detector component, which converts biochemical signals into optical, electrochemical, acoustic or thermal signals, proportionally to the amount of the analyte under investigation. 52,53 Regarding the analysis of allergic components in foods, several studies have been undertaken which showed the potential of biosensors for investigation of milk and peanuts, 35,47 fish and shrimps, 37,38 egg, 36 soy, and genetically modified soy [54][55][56] (Tables 2 and 3).…”
Section: Biosensors -Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous prospective applications of AuNP relate to the detection of biomolecules [13][14][15][16], including DNA strands [17][18][19][20][21][22][23][24][25], the design of photonic and bioelectronic devices, and the nanomedicine [26][27][28][29]. In the latter field, AuNP benefit medical diagnostics, cancer therapy, and contribute to imaging enhancements.…”
Section: Introductionmentioning
confidence: 99%
“…QCM technology has a huge field of applications in biochemistry and biotechnology. The availability for QCM to operate in liquid has extended the number of applications including the characterization of different type of molecular interactions such as: peptides (Furtado et al, 1999), proteins (BenDov et al, 1997), oligonucleotides (Hook et al, 2001), bacteriophages (Hengerer et al, 1999), viruses (Zhou et al, 2002), bacteria (Fung & Wong, 2001) and cells (Richert et al, 2002); recently it has been applied for detection of DNA strands and genetically modified organisms (GMOs) (Stobiecka et al, 2007). Despite of the extensive use of QCM technology, some challenges such as the improvement of the sensitivity and the limit of detection in high fundamental frequency QCM, remain unsolved; recently, an electrodeless QCM biosensor for 170MHz fundamental frequency, with a sensitivity of 67 Hz cm -2 ng -1 , has been reported (Ogi et al, 2009); this shows that the classical QCM technique still remains as a promising technique.…”
Section: Qcm For Biosensing Applicationsmentioning
confidence: 99%